Enzyme Release from Polyion Complex by Extremely Low Frequency Magnetic Field - Vlasova, Kseniya Yu. (Sci Rep, 2020)
Remote nano-magneto-mechanical actuation of magnetic nanoparticles (MNPs) by non-heating extremely low frequency magnetic field (ELF MF) is explored as a tool for non-invasive modification of bionanomaterials in pharmaceutical and medical applications. Here we study the effects of ELF MF (30–160 Hz, 8–120 kA/m) on the activity and release of a model enzyme, superoxide dismutase 1 (SOD1) immobilized by polyion coupling on dispersed MNPs aggregates coated with poly(L-lysine)-block-poly(ethylene glycol) block copolymer (s-MNPs). Such fields do not cause any considerable heating of MNPs but promote their rotating-oscillating mechanical motion that produces mechanical forces and deformations in adjacent materials. We observed the changes in the catalytic activity of immobilized SOD1 as well as its release from the s-MNPs/SOD1 polyion complex upon application of the ELF MF for 5 to 15 min. At longer exposures (25 min) the s-MNPs/SOD1 dispersion destabilizes. The bell-shaped effect of the field frequency with maximum at f = 50 Hz and saturation effect of field strength (between 30 kA/m and 120 kA/m at f = 50 Hz) are reported and explained. The findings are significant as one early indication of the nano-magneto-mechanical disruption by ELF MF of cooperative polyion complexes that are widely used for design of current functional healthcare bionanomaterials.